Blogowanie jako forma komunikacji: performatywność zjawiska szafiarzy - Wasilewska-Stawiak, Anna; Mikołajczyk, Kamila (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2013)
This article is dedicated to fashion blogging and its existence in the blogosphere. The authors present the history of fashion blogging in Poland, focusing on the performativity of fashion blogs expressed in the way in which the authors of web logs communicate with their readers, fans and in creating new fashion trends as part of street fashion.